Neuropathic Pain Components Are Common in Patients With Painful Cervical Radiculopathy, but Not in Patients With Nonspecific Neck-Arm Pain - Tampin, Brigitte; Slater, Helen; Briffa, Kathy (Lippincott Williams & Wilkins, 2013)
Objectives: The aim of this study was to investigate, using quantitative sensory testing (QST) parameters and the painDETECT (PD-Q) screening questionnaire, the presence of neuropathic pain (NeP) in patients with unilateral painful cervical radiculopathy (CxRAD) and in patients with unilateral nonspecific neck-arm pain associated with heightened nerve mechanosensitivity (NSNAP). Methods: All patients completed the PD-Q before QST. QST was performed bilaterally in the maximal pain area and the affected dermatome in 23 patients with painful C6 or C7 radiculopathy and in 8 patients with NSNAP following a C6/7 dermatomal pain distribution.Results: Patients with CxRAD demonstrated a significant loss of sensory function in mechanical (P≤0.021) and vibration sense (P≤0.003) on the symptomatic side compared with the asymptomatic side in both tested body regions and in the dermatome reduced cold detection (P=0.021) and pressure pain sensitivity (P=0.005), findings consistent with nerve root damage. These sensory alterations in the maximal pain area/symptomatic side are confirmative for the presence of NeP. In contrast to these QST data, only 30% of patients with CxRAD demonstrated a NeP component according to the PD-Q score. In patients with NSNAP, a significant side-to-side difference was demonstrated for warm detection threshold in the dermatome (P=0.030). The PD-Q score indicated that NeP components were unlikely in this group. Discussion: QST data suggest that NeP is likely to be observed in patients with painful CxRAD, but not in patients with NSNAP.